The syntactic licensing of ellipsis - Aelbrecht, Lobke (Linguistik aktuell, 2010)
This monograph presents a theory of ellipsis licensing in terms of Agree and applies it to several elliptical phenomena in both English and Dutch. The author makes two main claims: The head selecting the ellipsis site is checked against the head licensing ellipsis in order for ellipsis to occur, and ellipsis - i.e., sending part of the structure to PF for non-pronunciation - occurs as soon as this checking relation is established. At that point, the ellipsis site becomes inaccessible for further syntactic operations. Consequently, this theory explains the limited extraction data displayed by '